Peningkatan Kompetensi Siswa Kelas XII Kompetensi Keahlian Teknik Fabrikasi Logam SMK Negeri 2 Karang Baru pada Mata Pelajaran Produk Kreatif dan Kewirausahaan melalui Metode Kooperatif STAD - Aiyub (Multiverse: Open Multidisciplinary Journal, 2022)
This study aims to determine the effectiveness of the cooperative learning method of the Student Team Achievement Division (STAD) technique with the help of Creative Products and Entrepreneurship learning media in increasing the competence of class XII students in Metal Fabrication Engineering at SMK Negeri 2 Karang Baru in the subject of creative products and Entrepreneurship. This research is a classroom action research conducted in two cycles, with three meetings for each cycle. Each cycle in this study consists of four stages of implementation, namely planning, action, observation, and reflection. Data collection was carried out using affective observation sheet instruments, psychomotor observation sheets, as well as pre-test and post-test instruments. The affective observation sheet instrument is used to determine student competence in the affective aspect. The psychomotor observation sheet instrument is used to determine student competence in the psychomotor aspect. The pre-test and post-test instruments were used to determine students' competence in the cognitive aspect. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results showed that there was an increase in student competence in the affective, psychomotor, and cognitive aspects after the implementation of the STAD technique cooperative learning method with the help of Creative Product and Entrepreneurship learning media. In the affective aspect there was an increase of 48.21%, with the percentage of students' affective aspects at the first meeting of 56%, increasing to 83% at the sixth meeting. In the psychomotor aspect there was an increase of 22.15%, with an average psychomotor score of students on job sheet 1 of 67.66, increasing to 82.65 on job sheet 4. On the cognitive aspect there was an increase of 110.9%, with a score the average pre-test cycle 1 was 38.53, increasing to 81.26 in the post-test cycle 2.